Crystallographic and Orientation Features of Nanocrystals in Thin Film Condensates PbTe-Bi2Te3 on Glass Ceramics - Ya.P. Saliy; D.M. Freik; І.S. Bylina; M.O. Galushchak (Журнал нано- та електронної фізики)
With the help of the AFM-images analysis, using the discrete Fourier transformation, the autocorrelation function for the azimuthal angle φ and the amount of normal distributions for the polar angle ρ we have investigated the orientation process of structure formation of the nanocrystals in vapor-phase condensates of PbTe-Bi2Te3 solid solution on glass ceramics. It was detected that the substrate of glass ceramics does not depend on a particular orientation of crystallites. We determined that objects, which had been created by the planes of the cube, rhombic dodecahedron and their combinations, are formed on the sample surface. It was demonstrated the dependence between the average sizes of nanocrystals, their growth rate and the deposition time. We established the character of the dependence of the density distribution of the polar angle ρ and the Bi2Te3 content and duration of deposition.